Conflict Resolution and Its Implementation in Peacebuilding Study: The Perspective of the Hadiths of the Prophet Muhammad - Jaya Sukmana (ALSYS, 2026)
The escalating complexity of contemporary social, political, and religious conflicts demands ethical and humanistic approaches to resolution. This study aims to examine conflict resolution and peacebuilding principles from an Islamic perspective by drawing on the hadiths of Prophet Muhammad SAW through a narrative integrative literature review of academic sources and primary hadith texts. Thematic analysis identifies and synthesizes core concepts such as moral reconciliation, social empathy, restorative justice, and mediation rooted in rahmah and sulh. The findings indicate that this prophetic model prioritizes relational restoration over punishment and aligns with modern peacebuilding theories in multicultural global contexts. The study concludes that a prophetic ethics framework enriches peace theory by providing a value-based model of mediation and offers implications for interdisciplinary research that integrates religious, humanistic, and social perspectives to foster sustainable peace.